Mariupol: The Information Warfare - Svetlozar Kirilov (Медии и език, 2022)
The article deals with the main points of the information warfare between Russia and Ukraine related to Mariupol. Which side in the conflict is supported by the inhabitants of the city? Who is to be blamed for the death of civilians and destruction in Mariupol? To what extent the statements of the warring countries are consistent with the truth? The light is shed on the information coverage of four concrete events during the siege of Mariupol: the destruction of the Maternity Yard №3; the destruction of the theater; the fate of the civilians in Azovstal and the blocking of the ship “Tzarevna” in the port.